Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 1297 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Sus scrofa Linnaeus, 1758", "HasCoordinate is true", "HasGeospatialIssue is false", "BasisOfRecord is Specimen" ] } The dataset includes 1297 records from 62 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000526-170627171947987/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences